Synthesis, transfer and implementation of qualitative evidence to improve clinical practice and decision - Baixinho, Cristina (2022)
The worldwide dissemination of scientific production in the health area has been a contribution to evidence-based practice. However, it raises questions that are central to the synthesis of existing evidence and the use of the scientific method to do so, as well as the processes used to transfer and implement knowledge in clinical practice contexts, which facilitate decision-making. We aim to reflect on the methods that allow the synthesis, transfer and implementation of qualitative evidence for the improvement of practices and clinical decisions. Considering the great evolution in the number of qualitative studies, we will approach the elaboration of metasummaries and metasynthesis, as methodological approaches, to integrate, compare and synthesize the results of individual studies within a larger body of evidence, based on rigorous, reproducible methodologies and transparent, to determine what is known in a particular area or if there are evidence gaps that need to be investigated. Throughout the chapter, divided into six parts, the introductory conceptual question will be addressed, followed by the synthesis of qualitative evidence (metasynthesis and metasummaries) and the transfer and implementation of the qualitative synthesis, we present examples of practical cases, allowing then to proceed to the application of the proposal actually illustrated with practical cases. In the Final Considerations, we emphasize that the increase in Qualitative evidence is a challenge for the development of systematic reviews of qualitative studies, to increase consistency, reliability, rigor and safety in the use of the findings that emerge from these studies for an evidence-based practice , which is only possible with the involvement of all actors (researchers, academics, professionals and citizens).